Superconductivity a very short introduction - Blundell, Stephen 1967- (Very short introductions, 2009)
From the Publisher: Superconductivity-the flow of electric current without resistance in certain materials as temperatures near absolute zero-is one of the greatest discoveries of 20th century physics, but it can seem impenetrable to those who lack a solid scientific background. Outlining the fascinating history of how superconductivity was discovered, and the race to understand its many mysterious and counter-intuitive phenomena, Stephen Blundell explains in accessible terms the theories that have been developed to explain it, and how they have influenced other areas of science, including the Higgs boson of particle physics and ideas about the early Universe. This Very Short Introduction examines the many strange phenomena observed in superconducting materials, the latest developments in high-temperature superconductivity, the potential of superconductivity to revolutionize the physics and technology of the future, and much more. It is a fascinating detective story, offering invaluable insights into some of the deepest and most beautiful ideas in physics today.